Detection and antibiogram profile of diarrheagenic Escherichia coli isolated from two abattoir settings in northwest Ethiopia: a one health perspective - Abey, S.L.; Teka, M.; Bitew, A.B.; Molla, W.; Ejo, M.; Dagnaw, G.G.; Adugna, T.; Nigatu, S.; Mengistu, B.A.; Kinde, M.Z.; Berju, A.; Belete, M.A.; et al. (Springer, 2024)
Background: Diarrheagenic Escherichia coli (E. coli) is a zoonotic pathogen that contaminates abattoir workers, slaughter environments, slaughter equipment, and carcasses during abattoir processing. Infection with E. coli is associated with the consumption of contaminated food and water, and it is a potential threat to the health and welfare of both humans and animals. Hence, this study aimed to detect diarrheagenic E. coli and assess its antibiogram profile in two abattoir settings, in one health lens.